LIFE CYCLE OF DEVELOPMENT OF A RECORD-KEEPING SYSTEM IN ARMED FORSES OF UKRAINE - ORLOVSKYI, SERHII; STATSENKO, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article addresses the problem of selecting and adapting appropriate software development life cycle (SDLC) models for creating a digital record-keeping system in the Armed Forces of Ukraine. The research provides a comprehensive analysis of classical and modern SDLC models, including Waterfall, V-model, Incremental, Iterative, Spiral, Agile, and Scrum, with a focus on their advantages, limitations, and applicability to defense-related information systems. It highlights that an inappropriate methodological choice can negatively affect cost, flexibility, and functionality, emphasizing the importance of combining different approaches depending on the project phase and specific requirements. The authors propose a hybrid model that integrates elements of Waterfall and Iterative methodologies, enabling the development of a functional minimum viable product (MVP) with clear requirements and gradual expansion of features through iterative testing and refinement. Special attention is given to the challenges of transparency, traceability, monitoring, and uncontrolled changes during the development process, as well as to the complexity of error detection and debugging. The study also considers the integration of the accounting system with existing platforms such as ARMY+, outlining the need for a dedicated development team, well-structured documentation, and continuous testing at every stage. The proposed approach ensures flexibility in meeting evolving user needs while maintaining strict control over project planning and execution. A prototype, experimental deployment, and integration processes are described as distinct modules to provide a detailed view of the product’s life cycle. The findings of the research underline that hybrid methodologies are particularly suitable for military applications, where stability, adaptability, and reliability must be balanced. Ultimately, the study contributes to the methodological foundation for designing record-keeping systems in the defense sector and offers practical recommendations for their implementation in the Ukrainian Armed Forces.
Keywords: life cycle; software; module